The unspoken power of collage? Using an innovative arts-based research method to explore the experience of struggling as a teacher (UCL Press, 2019)
This article reports on the methodological approach taken in a doctoral study that explores what it means to be struggling as a teacher. Participants were established and experienced teachers and leaders in the secondary school system in England. A particular form of collage - where materials are placed rather than stuck - was used within the context of a research interview. Arts-based methods such as collage are gaining in popularity as they stimulate visual rather than linguistic thinking and offer the opportunity to express experiences as holistic, non-linear metaphors. Collage also has revelatory potential as it helps uncover that which participants cannot necessarily express in words alone. The author presents the analytical challenges of intermingling the verbal and visual data in her study by discussing the collages created by two participants. An analysis of those collages shows that factors influencing struggling can be both internal and external. Struggling was found to be experienced as a temporary fractured state. Struggling was expressed by participants as heightened bodily tensions with a predominantly negative emotional tone; it can also involve a damaged self-view and a reduced sense of controllability, and may lead to impaired performance.